Reactivity Of Incoporated Copper In Boronzsm-5 Zeolite For Methane Conversion To Higher Hydrocarbons - Mat, Ramli; Amin, Nor Aishah Saidina; Ramli, Zainab; W. Abu Bakar, W. Azelee (2000)
The modification of Boron ZSM-5 zeolite with copper for methane conversion to higher hydrocarbons is reported. Catalyst characterization was carried out using XRD and TPD. Direct substitution of boron for aluminium in the ZSM-5 structure result in slightly lower activity for methane conversion due to its lower acidity, however it improved the C5 + and C2-C4 yield. Introduction of copper species has improved the catalyst activity.